Learning Management of Inclusive Elementary School in Samarinda (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research aimed to identify the management of the inclusive learning process in elementary schools in Samarinda. This research focused on the inclusive learning process activities, including material, media, methods, models and learning activities in the classroom, the collaboration between students, relationships between students, teacher-student communication, and student learning outcomes. Data collection techniques used were observation, interviews, and documentation.  This qualitative descriptive study results can be concluded that the implementation of learning management in elementary schools in Samarinda has not been carried out maximally. This case is because the application of the inclusive learning in the elementary schools in Samarinda experiences several problems, including the lack of Special Advisory Teachers, the lack of socialization of learning management from the Educational Department to the schools, and the lack of cooperation that exists between schools and Special Schools.